PENGEMBANGAN VIDEO EDUKASI PADA MATERI TOLERANSI FASE C DI SD NEGERI LABUY ACEH BESAR - Fandra, Al Ghifari; Jailani (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2025)
This study aims to develop and examine the effectiveness of an educational video on tolerance material for Phase C at SD Negeri Labuy, Aceh Besar. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects included 26 fifth-grade students and one classroom teacher. The educational video, with a duration of 2 minutes and 43 seconds, was developed using simple content, engaging visuals, and clear audio, adjusted to the characteristics of elementary school students. Media validation was conducted by a subject-matter expert, a media expert, and the classroom teacher, along with trials involving students to measure their responses and understanding. The validation results indicated that the media fell into the “very feasible” and “feasible” categories, with an average feasibility percentage above 75%. Student responses were highly positive, showing increased interest and improved understanding of tolerance material. The use of the educational video created an interactive and enjoyable learning atmosphere while helping students comprehend the concept of tolerance more concretely. This study concludes that educational videos are effective and suitable learning media for enhancing students’ learning interest and learning outcomes in tolerance material at SD Negeri Labuy, Aceh Besar.